Biological aspects of Caligo teucer (Lepidoptera: Nymphalidae) with banana tree leaves - Silva,Carlos Alberto Domingues da (2021)
ABSTRACT Caligo teucer (Linnaeus, 1758) is widely distributed in Argentina, Bolivia, Brazil and Ecuador. The objective was to study biological aspects of Caligo teucer japetus Stichel, 1903 with banana leaves, Musa sapientium L. (Zingiberales: Musaceae), in the butterfly garden, under environmental conditions, and in the laboratory of biological control of insects at the Universidade Federal de Viçosa in Viçosa, Minas Gerais state, Brazil at 24 ± 2 oC, 68 ± 10% relative humidity and 12 hours photophase. The duration of the egg incubation, larvae, pupa and egg to adult periods of C. teucer japetus were, respectively, 11.8 ± 0.1; 53.9 ± 0.9; 17.9 ± 0.3 and 82.6 ± 1.0 days for females, and 11.8 ± 0.1; 50.3 ± 0.6; 18.4 ± 0.3 and 79.4 ± 0.6 days for males in cages in the laboratory. The longevity of C. teucer japetus adults was 26.0 ± 10.4 and 47.5 ± 8.7 for females and 24.7 ± 3.5 and 35.4 ± 15.7 for males in the butterfly garden and in laboratory cages, respectively. The high survival and the relatively short period of development of its immature stages confirm that banana leaves are an adequate food substrate for the development and survival of Caligo teucer japetus.